The city, COVID-19 and “the reverse overflow” - Zolezzi Chocano, Mario (2020)
The author considers the changes that can be unleashed in cities from a reflection on the Peruvian case. The starting point is the return process that thousands of people start from the declaration of total immobility and strict quarantine decreed by the government from the second half of March 2020. A quick review is made of the emergence of the urban centers in the current territory of Peru from the archaeological finds of several thousand years ago to the present. In this journey, some characteristics that differentiate them and the role that internal migrations have played are pointed out. In particular, the migrations that occurred from the second half of the 20th century until the emergence of the COVID19 pandemic and the inverse overflow that is causing from Metropolitan Lima to smaller urban centers and from these to towns and villages, as well as to rural areas. He concludes by pointing out the urgency of raising urban planning and territorial conditioning policies within the new scenario that opens from the effects and economic, demographic, social and cultural consequences of the COVID19 pandemic of migrants who are not well received.